Identification of Optimal Habitat of Spanish Mackerel (Scomberomorus commerson) Using a Species Distribution Modeling Approach in Tropical Waters - Zaidan Sastrawan; Sandipan Wijaya (Journal of Marine Fisheries, 2026)
Narrow-barred Spanish mackerel (Scomberomorus commerson) is one of the most economically important pelagic fish resources distributed throughout tropical and subtropical waters. The distribution of this species is influenced by various oceanographic factors, including sea surface temperature, chlorophyll-a concentration, salinity, water depth, and ocean current dynamics. Advances in remote sensing technology and Species Distribution Models (SDMs) have enabled more accurate and efficient identification of optimal habitats. This study aims to review the application of SDMs in identifying the optimal habitat of S. commerson in tropical waters based on recent scientific studies. A literature review approach was employed, focusing on publications that examined mackerel distribution and habitat modeling using Maximum Entropy (MaxEnt), Generalized Additive Models (GAM), Habitat Suitability Index (HSI), and Ensemble Modeling approaches. The review indicates that sea surface temperature and chlorophyll-a concentration are the most influential environmental variables affecting the distribution of S. commerson. The optimal environmental conditions generally occur within a sea surface temperature range of 26–30°C and chlorophyll-a concentrations between 0.2 and 1.0 mg m⁻³. SDM approaches provide effective spatial predictions for supporting sustainable fisheries management, identifying potential fishing grounds, and assessing the impacts of climate change on fish distribution. The integration of remote sensing data, oceanographic parameters, and advanced modeling techniques offers significant potential for improving fisheries resource management and habitat conservation in tropical marine ecosystems.